The Chemo-Sensitisation Effect Of Curcumin Against Low Dose Cisplatin On Non-Small Cell Lung Cancer (Nsclc) Stem Cells - Satar, Nazilah Abdul (2018)
Cancer stem cells (CSCs) represent a small subpopulation within a tumour that possesses the stem-like properties but are also initiating resistance towards cytotoxic agent which contribute to cancer relapse. A natural compound such as curcumin that contains high polyphenol has been found to possess chemo-sensitivity effect with an ability to sensitise the CSCs to the cytotoxic agents such as cisplatin. Therefore, the present study was designed to investigate the efficiency of curcumin as a chemo-sensitiser in lung CSCs and to analyse its inhibitory effect on CSCs activity using A549 and H2170 cell lines that belong to non-small cell lung cancer (NSCLC). The NSCLC cell lines cultures were treated with various concentrations of cisplatin and curcumin to obtain the inhibitory concentration (IC50) using 3-(4, 5-dimethylthiazol-2-yl)-2H-tetrazolium, inner salt (MTS) assay. The lung CSCs with phenotype CD166+EpCAM+ was isolated using fluorescence-activated cell sorting (FACS). The efficiency of curcumin to sensitise lung CSCs was observed on apoptosis and stemness characteristics including migration ability, colonies and spheroid formation. The mRNA level was analysed for genes involved in apoptosis and stemness using quantitative real time-polymerase chain reaction (RT-qPCR). Liquid chromatography mass spectrometry (LCMS) was used to evaluate the effect of curcumin on CSC niche. The results discovered that exposure of NSCLC cell lines to curcumin (10 μM – 40 μM) reduced the percentage of cells viability to an average of ~51% and ~54% in both A549 and H2170.